Parâmetros genéticos das características de crescimento e reprodutivas de ovinos Santa Inês - Oliveira, Isis Regina Santos de (2023)
The objective of this study was to estimate (co)variance components and genetic parameters for growth and reproductive traits in Santa Inês sheep raised in different states registered with the Associação Sergipana de Criadores de Caprinos e Ovinos (ASCCO). The database used was provided by this association and consisted of pedigree observations from 11 483 registered individuals, of which 2 238 were born within the program and had lambing records remaining in the pedigree matrix. After applying restrictions that excluded females with age at first lambing less than 399 days or greater than 1438 days, 820 animals with data for the traits age at first lambing (AFL), lambing interval (LI), interval between the first and second lambing (IFS), birth weight (BW), and weight at 60 days (W60) were retained for analysis. To obtain the (co)variance components and genetic parameters, Bayesian analysis was performed using a bicharacteristic animal model, employing the Multiple Trait Gibbs Sampling for Animal Models (MTGSAM) program. The model considered contemporary group and animal age as a fixed effect (as a (co)variable effect) for AFL, LI, IFS, BW and W60. To obtain the values of the (co)variance components and genetic parameters, Bayesian analysis was used under a two-characteristic animal model, using the Gibbs Sampler algorithm, with the aid of the Multiple Trait Gibbs Sampling for Animal Models (MTGSAM) program. The model considered contemporary group and animal age as a fixed effect (as a (co)variable effect) for AFL, LI and IFS characteristics. The characteristics BW and W60 considered the fixed effect of contemporary group and type of birth. The estimated heritability values (h²) for WB, W60, AFL, LI, and IFS were 0.11±0.0612, 0.18±0.0696, 0.028±0.0002, 0.25±0.1387, and 0.30±0.1432, respectively. The estimated heritability for AFL, BW, and W60 was considered low. The LI and IFS characteristics obtained the average estimated value, which leads to the conclusion that these characteristics can be used as selection criteria in a genetic improvement program for Santa Inês sheep. The estimated value for the correlation between the BW and W60 characteristics; AFL and LI; AFL and IFS was positive and equal to 0.31, 0.17, 0.18, respectively. For BW and AFL (- 0.55); BW and LI (-0.42); BW and IFS (-0.39); W60 and LI (-0.26); W60 and IFS (-0.37) were negative and their magnitudes were moderate to weak. However, the IPM and IPS characteristics show positive and very high trends, equal to 0.97. This value suggests that the best path to genetic gain is through indirect selection. The P60 and IPP characteristics also obtained a high correlation, equal to 0.98.